Performance of Local Government Regulations During the Pandemic to Improve the Economic Value of City Image in South Sulawesi - Andriyansah Andriyansah; Rulinawaty Rulinawaty (Fakultas Ekonomika dan Bisnis UNTAG Semarang, 2023)
This study aims to determine the performance of local governments in improving city image branding in South Sulawesi Province. This research uses a proportional sampling technique based on the area of the city so that the number of samples between one region and another will be different, using survey techniques in the form of questionnaires. For data analysis, this study used Structural Equation Modeling (SEM) with a total data of 265 samples. The hypothesis proves that the exogenous variables of city image branding consisting of regiocentric policy, street vendor performance, iconic tourism culinary and revisit destination have a positive influence on city image branding variables. This research contributes to the development of marketing science, the implication is that it provides input to stakeholders to increase the role of government performance on image branding.